Extension agent performance in transferring rice check technology in granary areas of Malaysia as perceived by farmers - Yusuf, Munifah Siti Amira (2019)
Rice is a staple food and highly demanded in Malaysia. The need and consumption of rice are rising in parallel with population growth. However, Malaysia’s food self-sufficiency and security are under threat as the adoption and application level of the rice check technology among farmers still require improvement. Performance of old granary reaches only about 50% of the targeted results despite 10 years of rice check technology dissemination. This is due to the extension agents’ performance in technology transfer. Therefore, the study was done in advance to avoid low performance at new granary would be just the same as the old granary. The purpose of this research was to determine the level of planning, implementing, monitoring and evaluation (IVs) and work performance (DV) of extension agents in granary areas of Malaysia, to determine the relationship between planning, implementing, monitoring and evaluation factors with work performance of extension agents in old and new granary areas, as well as to determine which factors contribute most to work performance of extension agents in old and new granary areas. The data were collected using established instruments and quantitative research method. Cluster sampling technique was used to meet 542 respondents from old (IADA KETARA and IADA Seberang Perak) and new (IADA Rompin and IADA Pekan) granary areas. Data were analysed using SPSS correlation and multiple regression procedure to examine the relationship of the extension agents’ competency with work performance. The findings showed that the level of planning is high while, implementing, monitoring and evaluation of extension agents in old and new granary areas are in a moderate level. Old and new granary have shown planning, implementing, monitoring and evaluation of extension agents have a positive correlation with work performance. This interpretation means that improvement of planning, implementing, monitoring and evaluation will cause to better work performance. However, the relationship for old granary shows that implementing, monitoring and evaluation have a moderate correlation (0.41<0.70), whilst, planning has a weak correlation (0.21<0.40). Multiple regression analysis explains only monitoring and evaluation has significant relationship with work performance. This variable explains 40.1% variance of the work performance (Adj.R2=0.401). In new granary areas, the correlation coefficients show that all the variables positively correlated and have moderate correlation with work performance. Moreover, multiple regression analysis explains three variables i.e. are planning, implementing, monitoring and evaluation have significant relationship with work performance. These variables explain almost 50% variance of the work performance (Adj.R2=0.491). Therefore, extension programmes in granary areas should focus on these three variables in order to increase work performance. To realise maximum production potential from both granaries, module and training should be provided to enhance the capacity of the extension agents in technology transfer.